Reconstruction of Islamic Religious Education Learning in Strengthening Moderation Education in Madrasas - Melda Diana Nasution; Hasanuddin Hasanuddin; Nurhalimah Nurhalimah (Jurnal Kawakib, 2026)
This study aims to analyze the reconstruction of Islamic Religious Education (PAI) learning to strengthen moderation education in madrasas. It examines the concept of moderation-based PAI learning, forms of learning reconstruction, implementation strategies, and their implications for students’ attitudes. The study employed a qualitative approach using a library research method by reviewing relevant literature on Islamic education and religious moderation. The findings reveal that moderation-based PAI learning emphasizes an inclusive, dialogical, and contextual educational paradigm that promotes balance, tolerance, and respect for diversity. Learning reconstruction is carried out through curriculum development, participatory pedagogical approaches, and authentic assessments covering cognitive, affective, and behavioral dimensions. The implementation strategy includes integrating moderation values into learning materials, applying reflective learning methods, and strengthening the teacher’s role as a facilitator of character development. The study concludes that reconstructing PAI learning contributes to fostering tolerant, inclusive, and anti-radical attitudes among students while supporting curriculum improvement, teacher competency development, and a culture of moderation in madrasas.